PERAN ISTERI DALAM MENUNJANG USAHA BUDIDAYA IKAN BANDENG DAN UDANG PECI DI DESA LAOSU JAYA KECAMATAN BONDOALA KABUPATEN KONAWE SULAWESI TENGGARA - Rosmawati Rosmawati; Irdam Riani; Abdul Muis Balubi (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2017)
This study aims to determine the role of wives in supporting fishery activities in the business of milkfish and shrimp fish cultivation in Laosu Jaya Village, Bondoala District, Konawe Regency, and Southeast Sulawesi. The populations in this study are fisherman households of milkfish and shrimp cultivators totaling 123 households. The number of samples selected is 36 households of fish and shrimp farmer’s.The results of this study indicate that the most dominant role of wife to do is to cultivate milkfish and shrimp as much as (38.89)%, crop sales (16.67%), salted fish (13.89)%, repairing the net (11.11%) and selling ice cubes, selling cakes, and making cakes 5.55% each. The high role of wife in conducting the activities of fish and shrimp culture business in Laosu Jaya Village Bondoala District Konawe Regency with the consideration that the fish nener dam and peci shrimp especially in Southeast Sulawesi is available and easy to get, that the ponds that do business is milk itself so that the sales proceeds obtained can meet the needs of household lifeThis study aims to determine the role of wives in supporting fishery activities in the business of milkfish and shrimp fish cultivation in Laosu Jaya Village, Bondoala District, Konawe Regency, and Southeast Sulawesi. The populations in this study are fisherman households of milkfish and shrimp cultivators totaling 123 households. The number of samples selected is 36 households of fish and shrimp farmer’s.The results of this study indicate that the most dominant role of wife to do is to cultivate milkfish and shrimp as much as (38.89)%, crop sales (16.67%), salted fish (13.89)%, repairing the net (11.11%) and selling ice cubes, selling cakes, and making cakes 5.55% each. The high role of wife in conducting the activities of fish and shrimp culture business in Laosu Jaya Village Bondoala District Konawe Regency with the consideration that the fish nener dam and peci shrimp especially in Southeast Sulawesi is available and easy to get, that the ponds that do business is milk itself so that the sales proceeds obtained can meet the needs of household life.